Potensi Antioksidan Ekstrak Cangkang Kepiting Rajungan (Portunus pelagicus) dari Pekalongan, Jawa Tengah, Indonesia - Ermawati, Nur; Mahbub, Khafid; Yuniarsih, Sri Mumpuni; Wiranti, Kharisma Wido; Octaviani, Felicia Aurelia (LPPM-KI - POLTEKKES PIM (Formerly AKAFARMA-AKFAR PIM, 2025)
Free radicals contribute to oxidative stress, which plays a key role in degenerative diseases. Antioxidants neutralize free radicals, preventing cellular damage. This study evaluates the antioxidant activity of Portunus pelagicus shell extract from Wonokerto, Pekalongan Regency, using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) method. Extraction was performed through demineralization, deproteinization, and maceration with virgin coconut oil. Phytochemical analysis confirmed the presence of terpenoids, which are known for their antioxidant properties, but Thin Layer Chromatography (TLC) did not detect astaxanthin. Antioxidant activity testing at concentrations of 5, 10, 50, and 100 ppm resulted in an IC50 value of 549.40 ppm, indicating very weak antioxidant potential. The absence of astaxanthin and the weak activity may be due to extraction method limitations, solvent choice, or low concentrations of active compounds. These findings highlight the need for optimized extraction techniques to enhance the bioactive potential of crab shell-derived compounds. This study contributes to marine biowaste utilization and provides insights into improving antioxidant properties for pharmaceutical and nutraceutical applications.